Serial-Measured Versus Estimated Creatinine Clearance in Patients with Non-Small Cell Lung Cancer Receiving Cisplatin-Based Chemotherapy - 張基晟(Gee-Chen Chang); 楊宗顯(Tsung-Ying Yang); 施純明(Chuen-Ming Shih); 林隆堯(Long-Yau Lin); 李鴻森(Hong-Shen Lee); 江自得(Chi-Der Chiang) (Journal of the Formosan Medical Association, 2003)
Cisplatin-based chemotherapy is the main therapy for patients with advanced stage non-small cell lung cancer (NSCLC). The dose of cisplatin is adjusted according to the patient's renal function. Calculation of creatinine clearance (CCr) by 24-hour urine collection is the most common method for estimating the glomerular filtration rate but is time-consuming and inconvenient. Estimation of CCr using the Cockcroft-Gault formula has been suggested to be accurate, reproducible, and less costly. This study compared CCr values obtained by measured and estimated methods during cisplatin-based chemotherapy in NSCLC patients in Taiwan. A total of 92 patients (58 men, 34 women) with advanced NSCLC who completed 6 cycles of chemotherapy participated in the study. The dose of cisplatin per cycle was 80 mg/m(2) every 28 days, reduced to 50 mg/m(2) if CCr was 30 to 60 mL/min by the measured method. When urine collection was finished, serum and urine creatinine levels were measured simultaneously. Estimated values were calculated before each cycle of chemotherapy. The mean measured CCr was 85.2 mL/min, 25.7 mL/min higher than the mean estimated value. CCr values obtained by both methods were significantly reduced during the 6 cycles of chemotherapy. There was no significant difference in CCr values between patients aged < 65 years or >/= 65 years (-19.9 vs -15.1 mL/min, p = 0.15). Using a cut-off of measured CCr >/= 60 or < 60 mL/min, agreement on the dosage for both methods was 51% for all patients, 77.7% for patients < 65 years, and 26.7% for patients >/= 65 years. The Cockcroft-Gault formula underestimated measured CCr by about 25 mL/min in this study. Cisplatin-based chemotherapy reduced CCr, with no significant difference between older and younger patients. Use of the estimated method would result in significant under-dosing, especially for patients >/= 65 years old.